2006
DOI: 10.1055/s-2005-872976
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Sclerosing Hemangioma with Pulmonary Metastasis

Abstract: We present a case of pulmonary sclerosing hemangioma with multiple involvements. Pulmonary sclerosing hemangioma is a relatively rare neoplasm. Although it is thought to be benign, cases with lymph node metastasis or multiple pulmonary involvement have been reported in clinical settings. To date, no case has been reported with mortality due to sclerosing hemangioma, however its clinical characteristics of multiple spread and lymphnode metastasis have not yet been elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…1,2 This tumor is generally regarded as benign but rare cases involving lymph node metastasis [3][4][5][6][7] or multifocal lesions [8][9][10] have been reported. However, there have been no reports of pulmonary SH with pleural dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This tumor is generally regarded as benign but rare cases involving lymph node metastasis [3][4][5][6][7] or multifocal lesions [8][9][10] have been reported. However, there have been no reports of pulmonary SH with pleural dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PSH may be low-grade malignancy, since cases of lymph node and lung metastases have been reported. Thus, FDG PET/CT could be useful for the differential diagnosis of low-grade malignancy of PSH, particularly when the SUVmax of PSH exceeds 2.5, or when lymph node and lung metastases are displayed on PET/CT images (9)(10)(11)(12)(13)(14), which would be of great assistance in the clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have suggested that certain benign pulmonary tumors, such as PSH, may be low-grade malignancies, since cases of lymph node and lung metastases have been reported (9)(10)(11)(12)(13)(14), or that the malignant transformation of lung benign tumors may be possible, such as the transformation of pulmonary hamartoma into adenocarcinoma, sarcoma or squamous cell carcinoma (15)(16)(17). Thus, it is also important to compare and analyze the characteristics of 18 F-FDG PET/CT in benign lung tumors and to evaluate their metabolic activities to choose the proper clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered a benign malady, but several cases with lymph node metastasis or multifocal pulmonary involvement have been reported (4,5). The origin of PSH is controversial; however, recent studies on the expression levels of estrogen receptors and the markers of type II pneumocytes, such as TTF-1, MUC1, Thomsen- Table V.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological diagnosis can be confirmed through the presence of a mixture of the 4 major histological patterns and through the distinctive cellular components (surface-lining cuboidal and stromal-pale tumor cells) found within a single tumor (1)(2)(3). Several cases with lymph node metastasis or multifocal lung involvement have been reported (4,5), but did not have a bad prognosis. It is therefore thought that the nature of this tumor is between benign and malignant.…”
Section: Introductionmentioning
confidence: 99%